Transmissibility of Broad bean wilt virus 1 by aphids: influence of virus accumulation in plants, virus genotype and aphid species - Ferriol, Inmaculada; Rubio, Luis; Pérez-Panadés, J.; Carbonell, Emilio A.; Davino, Salvatore; Belliure, Belén (2017)
Broad bean wilt virus 1 (BBWV-1) is transmitted by several aphid species in a non-persistent manner. Transmission efficiency by vectors is a key factor for understanding virus epidemiology and applying disease control measures based on limiting virus spread. We evaluated the transmission rates of two genetically divergent BBWV-1 isolates (PV-132 from USA and Ben from Spain) infecting broad bean (Vicia faba L.) by isofemale lines of nine aphid species from eight different genera collected in Spain. Our analyses showed that: (a) the virus concentration in the source plant was a key factor in BBWV-1 transmissibility; (b) The Spanish isolate Ben was transmitted more efficiently than the American isolate PV-132 by most aphid species, but this was only due to the higher accumulation of Ben in plants, as both isolates had similar transmissibility after adjusting virus concentration and (c) The transmission rate varied greatly between the different aphid species.